Screening of soybean genotypes for antixenosis against Spodoptera litura: Screening of soybean genotypes for antixenosis against Spodoptera litura - VANGALA RAJESH,; LOKESH KUMAR MEENA,; SANJAY GUPTA,; M SHIVAKUMAR,; V NATARAJ,; VIRAJ G KAMBLE,; R RAMTEKE,; SUBHASH CHANDRA,; R N SINGH,; A N SHARMA, (Journal of Oilseeds Research, 2020)
Among 95 soybean genotypes screened against Spodoptera litura, 2 genotypes viz., Hara Soya and G5P22exhibited strong antixenosis, 11 genotypes exhibited moderate antixenosis. Whereas, 40 genotypes and 42 genotypes expressed slight antixenosis and preference host respectively.